A Model of a High Level Chess Concept "Attack on a weak square" - Nairi P. Hakobyan; Vachagan G. Vahradyan (Изд-во НАН РА)
Subjective chess concept “attack on a weak square” was formalized. The task is divided into three terms – “weak square”, “square under attack”, “pin”. To analyze these concepts the mathematical apparatus of fuzzy logic is applied and an acceptable comparison between computer and human estimations of a "weak square" for certain positions is demonstrated.
Keywords: Mathematics; Computer software